2022
DOI: 10.1038/s41598-022-05957-7
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of repeated breathhold and impact of breathhold failure in whole breast and regional nodal irradiation in prone crawl position

Abstract: In whole breast and regional nodal irradiation (WB + RNI), breathhold increases organ at risk (OAR) sparing. WB + RNI is usually performed in supine position, because positioning materials obstruct beam paths in prone position. Recent advancements allow prone WB + RNI (pWB + RNI) with increased sparing of OARs compared to supine WB + RNI. We evaluate positional and dosimetrical impact of repeated breathhold (RBH) and failure to breathhold (FTBH) in pWB + RNI. Twenty left-sided breast cancer patients were scann… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…This trend is similar to the outcomes of earlier WBI + LNI studies on the effects of DIBH in the prone crawl position, with a 40% heart dose reduction compared to SB 15 . Previous studies at our center further confirmed the reproducibility of DIBH for both prone dive (WBI) 38 and prone crawl (WBI + LNI) 39 …”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This trend is similar to the outcomes of earlier WBI + LNI studies on the effects of DIBH in the prone crawl position, with a 40% heart dose reduction compared to SB 15 . Previous studies at our center further confirmed the reproducibility of DIBH for both prone dive (WBI) 38 and prone crawl (WBI + LNI) 39 …”
Section: Discussionsupporting
confidence: 89%
“… 15 Previous studies at our center further confirmed the reproducibility of DIBH for both prone dive (WBI) 38 and prone crawl (WBI + LNI). 39 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation